Filling a knowledge gap of two centuries: rediscovery of Eugenia subamplexicaulis (Myrtaceae) with notes on its morphology, distribution and conservation - Fernandes, Thiago; Faria, Jair Eustáquio Quintino; Proença, Carolyn Elinore Barnes; Braga, João Marcelo Alvarenga (Phytotaxa, 2020)
Eugenia subamplexicaulis belongs to Eugenia sect. Pilothecium and was described based on a collection made in São Paulo state by C.F.P. von Martius in 1817. After that, no other collection of this species was made until May 2018, over 200 years later, when this species was rediscovered in the rocky formation Monumento Natural da Pedra de Itaocaia, a protected area located in Rio de Janeiro state. This study provides an enhanced morphological description of the species, notes on its morphological affinities, geographic distribution and conservation status. The species can be recognized by its subsessile leaves, dichasial inflorescences and oblate fruits with up to three seeds. The fruits are described for the first time, since the original description was based only on a single flowering specimen. Additionally, the first photographic documentation of the live plant in its habitat is presented.